Q: What is 1 plus 2 plus 3 plus 4 plus 5 plus 6 plus 7 plus 8 plus 9 plus 9 plus 9 plus 9 plus 9 plus 0?

Write your answer...

Submit

Related questions

1+-1= 0. 0+1=1 1+2=3 ps 3+4=7 7+8=15

8/8 - 1 + 3 - 1 + 0 = 1-1+3-1+0 = 0 + 3 - 1 + 0 = 3 - 1 = 2

100101 1 times 2^0 = 1 PLUS 0 times 2^1 = 0 PLUS 1 times 2^2 = 4 PLUS 0 times 2^3 = 0 PLUS 0 times 2^4 = 0 PLUS 1 times 2^5 = 32 EQUALS 37

0=(9)2-(9-3)(root of 4)+3(2)

43

-2 -1 0 1 2

The answer is 0.

0+0+2=2 2 divided by 3 = 2/3

y = 1 2 x 1 - 2 = -3 x 1 + 3 2 - 2 = -3 + 3 0 = 0

x2 + x + 1 = 0 ∴ x2 + x + 1/4 = -3/4 ∴ (x + 1/2)2 = -3/4 ∴ x + 1/2 = ± √(-3/4) ∴ x = - 1/2 ± (i√3) / 2 ∴ x = (-1 ± i√3) / 2

X= -1 1*2 0-1 -1-2 -3/3 -1

-1+1+2+3+5= 10 First, you move 1 left of "0", which is -1. Then, you move 1 digit to the right, which puts you back at "0". Add 2, add 3, and add 5. The sum is 10.

It is closer to 1 than it is to 0.

2x2 + 7x + 3 = (2x + 1)(x + 3)If 2x2 + 7x + 3 = 0 then:(2x + 1)(x + 3) = 0⇒ (2x + 1) = 0 → x = -1/2or (x + 3) = 0 → x = - 3

A huge number. 0 + 1 + 2 = 3 0 + 2 + 1 = 3 1 + 0 + 2 = 3 1 + 2 + 0 = 3 2 + 0 + 1 = 3 2 + 1 + 0 = 3 -0 + 1 + 2 = 3 -0 + 2 + 1 = 3 1 - 0 + 2 = 31 + 2 - 0 = 32 - 0 + 1 = 32 + 1 - 0 = 3 0 - 1 + 3 = 2 0 + 3 - 1 = 2 -1 + 0 + 3 = 2 -1 + 3 + 0 = 2 3 + 0 - 1 = 2 3 - 1 + 0 = 2 -0 - 1 + 3 = 2-0 + 3 - 1 = 2-1 - 0 + 3 = 2-1 + 3 - 0 = 23 - 0 - 1 = 23 - 1 - 0 = 2 0 - 2 + 3 = 1 0 + 3 - 2 = 1 -2 + 0 + 3 = 1 -2 + 3 + 0 = 1 3 + 0 - 2 = 1 3 - 2 + 0 = 1 -0 - 2 + 3 = 1-0 + 3 - 2 = 1-2 - 0 + 3 = 1-2 + 3 - 0 = 13 - 0 - 2 = 13 - 2 - 0 = 1 1 + 2 - 3 = 0 1 - 3 + 2 = 0 2 + 1 - 3 = 0 2 - 3 + 1 = 0 -3 + 1 + 2 = 0 -3 + 2 + 1 = 0 For each of these equations there is a counterpart in which all signs have been switched. For example 0 + 1 + 2 = 3 gives -0 - 1 - 2 = -3and so on. Now, all of the above equations has three numbers on the left and one on the right. Each can be converted to others with two numbers on each side. For example:the equation 0 + 1 + 2 = 3 gives rise to0 + 1 = 3 - 20 + 1 = -2 + 30 + 2 = 3 - 10 + 2 = -1 + 31 + 2 = 3 - 01 + 2 = -0 + 3-0 + 1 = 3 - 2-0 + 1 = -2 + 3-0 + 2 = 3 - 1-0 + 2 = -1 + 31 + 2 = 3 + 01 + 2 = +0 + 3 As you can see, the number of equations is huge!

Negative plus a negative is a negative. Ex. -1+-1=-2 Negative times a negative is a positive. -2*-2=4 But a negative [minus] plus a positive [plus] can be minus, zero or plus: For example, -3 + 2 = -1 -3 + 3 = 0 -3 + 4 = +1

10 + 9 + 8 + 7 + 6 + 5 + 4 + 3 + 2 + 1 + 0 = 55

x2 + 6x + 1 = 0 x2 + 6x + 9 = 8 (x + 3)2 = 8 x + 3 = ± 2√2 x + 3 = -3 ± 2√2 x ∈ {-3 - 2√2, -3 + 2√2}

9

1/2 , 3/2

10 + 9 + 8 + 7 + 6 + 5 + 4 + 3 + 2 + 1 + 0 = 55

1+1+1+1x0 1+1+1+0 1+1+1 3

It is a quadratic equation and the values of x are -1/2 or -2/3Do you mean 12x2+14x+4 = 0If so then x = -2/3 and x = -1/2

no it's 0. Na = +1 O = -2 Na2O = +1(2) + (-2) = 0

(-1, 0)